Sie sind auf Seite 1von 2

Expand (x 3)9 in ascending power of x

First method (by Binomial Expansions)

x
(x 3) = 31
3

x
= 3 1
9

9 x 9 x 2 9 x 3 9 x 4

= 3 1 ...
1 3 2 3 3 3 4 3

= 39 1 3x

9.8 x 2 9.8.7 x 3 9.8.7.6 x 4



.
..
2.1 9 3.2.1 27 4.3.2.1 81

= 19683 + 59049x 78732x2 + 61236x3 30618x4 +

Second method (by Maclaurins series)


Let h(x) = (x 3)9, h(0) = 19683
h(x) = 9(x 3)8, h(0) = 59049
h(x) = 72(x 3)7, h(0) = 157464
h(3)(x) = 504(x 3)6, h(3)(0) = 367416
h(4)(x) = 3024(x 3)5, h(4)(0) = 734832

By Maclaurins series,
2
3
4
h(x) = 19683 + 59049x + x (157464 ) + x (367416 ) + x (734832 ) +

2!

3!

4!

= 19683 + 59049x 78732x2 + 61236x3 30618x4 +


Note:
n n
C r
r
2
3
Maclaurin series: f(x) = f(0) + xf(0) + x ( f ' ' (0)) + x ( f ' ' ' (0)) +

2!

3!

Exercise (EXPAND THE FOLLOWING)

1.

(2x 6)6

2.

sin x

3.

ln(1 + x)

4.

ex

5.

cos x

6.

3 1
x 2
x

7.

4 2
x
x

8. (1 + 2x + x2)4
9. (3 5x)(1 + 3x)4
10. (1 + 2x x2)(4 + x)6
11.

1 x
1 2x